Deaths Rates in Public Hospitals of Eastern Cape Province of South Africa - A Nge Okwe; B Van den Borne; P Bovet; B Longo-Mbenza; DL Buso Buso; M Mzingelwa (Tehran University of Medical Sciences, 2012)
Background: South Africa (SA) is experiencing a rapid epidemiologic transition as a consequence of political, economic and social changes. In this study we described, based on hospital data, the mortality patterns of Non communicable Diseases (NCD), Communicable Diseases (CD), the NCD/CD ratios, and the trends of deaths.Methods: We conducted a cross-sectional survey of all deaths occurring in several public hospitals in the Eastern Cape Province of SA between 2002 and 2006. Causes of deaths were coded according to the ICD 10 Edition.Results: A total of 107380 admissions responded to the inclusion criteria between 2002 and 2006. The crude death rate was 4.3% (n=4566) with a mean age of 46±21 years and a sex ratio of 3.1 men (n=3453): 1 woman (n=1113). Out of all deaths, there were 62.9% NCD (n=2872) vs. 37.1% CD (n=1694) with NCD/CD ratio of 1.7. The ratio NCD/CD deaths in men was 1.3 (n=1951/1502) vs. NCD/CD deaths in women of 1.9 (n=735/378). The peak of deaths was observed in winter season. The majority of NCD deaths were at age of 30-64 years, whereas the highest rate of CD deaths was at age< 30 years. The trend of deaths including the majority of NCD, increased from 2002 to 2006. There was a tendency of increase in tuberculosis deaths, but a tendency of decrease in HIV/AIDS deaths was from 2002 to 2006.Conclusion: Non-communicable diseases are the leading causes of deaths in rural Eastern Cape province of SA facing Post-epidemiologic transition stages. We recommend overarching priority actions for the response to the Non-communicable Diseases: policy change, prevention, treatment, international cooperation, research, monitoring, accountability, and re-orientation of health systems.